KREATIVE MILIEUS UND INTERKOMMUNALE KOOPERATION ALS TEILSTRATEGIEN DER REGIONALPOLITIK/ ERFAHRUNGEN AUS DEN LETZTEN 30 JAHREN - Jörg, Maier; Breitenfelder, Michael (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
Cooperation at municipality level is a long known solution for the management of existing problems. Creative milieus allow cooperation on the ground of existing trust. Cooperations with upper administrative tiers on qualitative grounds, like regional tourism advertisements or image campaigns at regional level, seem to yield to more results than quantitative cooperations based on daily challenges. This is also demonstrated by the experiences of the municipal cooperations of the settlements of the A9 ‒ Fränkische Schweiz business community, which show, on the one hand, that such cooperations already exist, even though to a limited extent (mostly only at the level of administrative associations), and, on the other hand, that such cooperations are often unsuccessful. There are several reasons for this: leaders of the municipal administration often say that new tasks at the level of joint administration are not reasonable or possible, due, among other things, to bureaucratic obstacles. Nevertheless we can see examples from other regions for innovative solutions at intermunicipal level. This requires in the first place, “makers”, i.e. dedicated persons within the municipal administration, with strong network relations and adequate information within the region. It is a frequently mentioned problem recently that the relations among the respective municipalities or the knowledge of the other municipalities are often limited to the person of the mayor and event the leaders of the neighbouring municipalities may not know each other personally. This calls for a “functional reform”, i.e. project-based cooperation according to the areas/topics of daily operation, in order to exploit possibilities like savings and enhanced work efficiency. Freely available personal resources could be utilised, in addition to the classic administrative tasks, in new areas, allowed by the reasonable concentration of the municipal tasks. Of course there are fields where such cooperations do not seem possible, e.g. protection against fire.